NILAI-NILAI PENDIDIKAN ISLAM DALAM SILEK TUO DI MINANGKABAU - Muhammad Ziad Imtiyaas; Ahmad Rivauzi (LPPM Universitas Ekasakti, 2024)
Islamic education comprises three main aspects: aqidah (creed), ibadah (worship), and akhlak (morality). These aspects form the foundation of Silek Tuo, a traditional martial art of Minangkabau. However, over time, the Islamic educational values within Silek Tuo have begun to fade. One contributing factor is the declining presence of tua silek (elder masters), leading to a disruption in the transmission of these values to future generations. Additionally, Silek Tuo has lost its appeal among the community, particularly among the youth, who tend to prefer foreign martial arts such as taekwondo, karate, judo, kung fu, and others. These martial arts prioritize competition over the understanding and internalization of the values inherent in Silek Tuo. Another factor is the diminishing love for ancestral culture, resulting in the loss of regional identity, especially in Minangkabau. Consequently, the dakwah (Islamic propagation) values within Silek Tuo are not being effectively conveyed.